2009
DOI: 10.1021/bm801502r
|View full text |Cite
|
Sign up to set email alerts
|

Glucose-Sensitive Microcapsules from Glutaraldehyde Cross-Linked Hemoglobin and Glucose Oxidase

Abstract: We have fabricated the glucose-sensitive protein hollow microcapsules from hemoglobin (Hb) and glucose oxidase (GOx) via layer-by-layer technique with glutaraldehyde (GA) as a cross-linking agent. We demonstrated the coupled enzymatic reactions between Hb and GOx within capsules by means of CLSM. The real-time monitoring of the consumption of glucose may be useful for the design of a glucose sensor. Furthermore, to further study the effect of glucose on the capsules, we investigated the wall permeability of (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
79
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(79 citation statements)
references
References 35 publications
0
79
0
Order By: Relevance
“…They found that the (GOx-hemoglobin)5 microcapsules became permeable to dextran in the presence of 100 mM glucose, although dextran was impermeable without glucose. 122 They also prepared GOx-catalase LbL layers on the surface of an insulin microcrystal, and found that the dissolution rate of insulin increased in response to glucose. 123 The effects of glucose were explained by the local pH changes induced by the GOx-catalyzed reaction of glucose.…”
Section: ·2 Controlled Release From Lbl Microcapsulesmentioning
confidence: 99%
“…They found that the (GOx-hemoglobin)5 microcapsules became permeable to dextran in the presence of 100 mM glucose, although dextran was impermeable without glucose. 122 They also prepared GOx-catalase LbL layers on the surface of an insulin microcrystal, and found that the dissolution rate of insulin increased in response to glucose. 123 The effects of glucose were explained by the local pH changes induced by the GOx-catalyzed reaction of glucose.…”
Section: ·2 Controlled Release From Lbl Microcapsulesmentioning
confidence: 99%
“…Polymer containers based on the LbL technique have recently attracted high interest for a variety of different applications, ranging from drug delivery systems and targeted gene therapy to biosensor devices. [19,20] To date, capsules have been made of synthetic and biodegradable polyelectrolytes, [21,22] comprising natural molecules such as oligonucleotides [23] and proteins, [24,25] which demonstrates the high versatility of LbL assembly. Using standard LbL preparation techniques [18] and employing supercharged proteins E57 and K48 as building blocks, we generated capsules exhibiting the following wall structure: (DEXS/pARG)(E57/K48) 3 (E57/K48 AF488 )E57, where DEXS denotes dextran sulfate and pARG poly-(L-arginine), two charged biodegradable polymers made from naturally occurring monomers (see Supporting Information).…”
Section: Capsule Preparation and Characterizationmentioning
confidence: 99%
“…Considerable effort has been devoted to achieving this goal via incorporation of functional materials or nanoparticles into the microcapsule shell to control the release of the contents of the microcapsules through the application of an external stimulus, 1-3 such as pH, 4-7 temperature, [8][9][10] light, [11][12][13] ultrasound, [14][15][16][17] glucose 18,19 and magnetic field, [20][21][22] at the appropriate time. Significant progress has been achieved to develop such controlled release methods; however, methods with better controllability are still in demand.…”
Section: Introductionmentioning
confidence: 99%